2015
DOI: 10.1111/hepr.12609
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation‐associated upregulation of the sulfated steroid transporter Slc10a6 in mouse liver and macrophage cell lines

Abstract: Aim Slc10a6, an incompletely characterized member of the SLC10A bile acid transporter family, was one of the most highly-induced RNA transcripts identified in a screen for inflammation responsive genes in mouse liver. This study aimed to elucidate a role for Slc10a6 in hepatic inflammation. Methods Mice were treated with LPS (2mg/kg) or IL-1β (5mg/kg) for various time points. Cells were treated with LPS (1μg/ml) at various time points, with cell signaling inhibitors, nuclear receptor ligands and Slc10a6 subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
(94 reference statements)
0
6
1
Order By: Relevance
“…We identified several genes, which determine cholesterol flux, as upregulated in liver ECs of GF mice relative to their CONV-R counterparts ( Figure 2 C). In contrast to a previous study showing the regulation of the Na + -dependent bile acid transporter solute carrier family 10 member 6 ( Slc10a6 ) via lipopolysaccharide signaling, depending on the nuclear receptor farnesoid X receptor (FXR) and the retinoid X receptor ( Kosters et al., 2016 ; Sawkat Anwer and Stieger, 2014 ), we found increased expression of Slc10a6 at GF housing conditions. In line with increased plasma lipoprotein levels at chow diet at GF housing conditions ( Kiouptsi et al., 2019 ), expression of Tsc22d1 , encoding a transcription factor that is critically involved in the formation of high-density lipoprotein (HDL) particles ( Jäger et al., 2014 ), was increased in the hepatic endothelium of GF mice.…”
Section: Resultscontrasting
confidence: 99%
“…We identified several genes, which determine cholesterol flux, as upregulated in liver ECs of GF mice relative to their CONV-R counterparts ( Figure 2 C). In contrast to a previous study showing the regulation of the Na + -dependent bile acid transporter solute carrier family 10 member 6 ( Slc10a6 ) via lipopolysaccharide signaling, depending on the nuclear receptor farnesoid X receptor (FXR) and the retinoid X receptor ( Kosters et al., 2016 ; Sawkat Anwer and Stieger, 2014 ), we found increased expression of Slc10a6 at GF housing conditions. In line with increased plasma lipoprotein levels at chow diet at GF housing conditions ( Kiouptsi et al., 2019 ), expression of Tsc22d1 , encoding a transcription factor that is critically involved in the formation of high-density lipoprotein (HDL) particles ( Jäger et al., 2014 ), was increased in the hepatic endothelium of GF mice.…”
Section: Resultscontrasting
confidence: 99%
“…A previous study showed that Slc10a6 mRNA levels were significantly induced by LPS in the mouse liver and WAT ( Kosters et al, 2016 ). To further investigate the response of peripheral intracrine tissues to inflammation, gene expression analysis of steroid sulfate carriers was performed in LPS-induced 3T3-L1 adipocytes and mouse adipose tissues.…”
Section: Resultsmentioning
confidence: 99%
“…A global gene expression analysis in mice demonstrated that Soat is among the most strongly induced genes by LPS in the liver and macrophages ( Kosters et al, 2016 ). In addition, Slc10a6 mRNA expression was upregulated in the liver of mice treated with the cytokine IL-1β.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations